Description Learning Difficulties of Students in Online Learning on ICT-Based IPS Research Courses - Rachmat Setiawan; Sekar Purbarini Kawuryan; Ali Mustadi (AL-ISHLAH: Jurnal Pendidikan, 2022)
Online learning causes learning difficulties experienced by PGSD FIP UNY students in ICT-based Social Studies Research courses. There is still very little literature from reputable national journals that discuss the analysis of learning difficulties in basic education as the background for this literature review. The purpose of this review is to analyze the learning difficulties experienced by students. The method uses descriptive qualitative research. Data collection techniques by observation and interviews in UNY. Testing the validity of the data used by triangulation of sources. The results of this study explain the learning difficulties experienced by students in online learning, namely: 1) there are technical signal problems and inability in online learning 2) there are obstacles to interacting in online learning 3) there are supporting obstacles to Stakeholders in learning on line. Learning difficulties experienced by students need to be resolved with cooperation between the government, parents, and students them selves so that education continues to run effectively and efficiently.